Editorial: Apocalyptic Imaginings Journal for Religion, Film and Media - Alexander Darius Ornella (Journal for Religion, Film and Media, 2019)
This editorial shows the impact of apocalyptic images and topoi referring to the ongoing Brexit-process in the United Kingdom and, thereby the editorial builds a bridge to the articels of this issue that analyse how diverse contemporary media adapt, critically question and represent apocalyptic imageries.